(untitled) (Research, Society and Development, 2021)
The crisis caused by Sars-CoV-2, which causes Covid-19, is an ecological crisis. The agency of effective actions for its control and overcoming requires a systemic understanding of the phenomenon and the concept of syndemic is more appropriate as it encompasses such complexity. Thus, we discuss the rupture of sociometabolism between human being/nature in the midst of alienated relations of production carried out in the market and how the movement of ecovillages contributes to reconfigure the human being/nature relationship based on ecological bases. The agricultural and construction industries, which model the spatial distribution in the countryside and in the city based on the logic of capital accumulation, exert strong pressure on ecosystems and are taken as a reference in this investigation. The experiences of four ecovillages, through ethnographic-inspired research, reveal an organizational type that, once oriented towards self-sufficiency mediated by self-managed communal work, has the potential to reconfigure the human/nature relationship, mitigating the embarrassments of the market enclave and the consequences of the syndemic via polyculture practices, bio-constructions and dissemination of their ideals for their militancy and ecological education, while touching on the fundamental points of the crisis, that is, socio-environmental degradation.